2017
DOI: 10.1177/0969733017727153
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’, nursing students’, and nursing instructors’ perceptions of professional values: A comparative study

Abstract: There is need for plans to increase nurses' awareness of certain professional duties and improve their professional performance in all areas alongside their care duties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
93
3
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 41 publications
11
93
3
10
Order By: Relevance
“…As in other research (Clark ), the students granted more importance to the professional values compared to the nurses. These findings of decreasing professional values do not coincide with other studies (Bijani et al ; Gallegos & Sortedahl ; Monroe, ; Poorchangizi et al ) where the opposite effect was observed. However, our findings about the different appraisal of professional values among students and nurses were recently confirmed in a similar study conducted in Iran, which included the vision of instructor nurses, finding significant differences among the three groups in all the domains analysed.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…As in other research (Clark ), the students granted more importance to the professional values compared to the nurses. These findings of decreasing professional values do not coincide with other studies (Bijani et al ; Gallegos & Sortedahl ; Monroe, ; Poorchangizi et al ) where the opposite effect was observed. However, our findings about the different appraisal of professional values among students and nurses were recently confirmed in a similar study conducted in Iran, which included the vision of instructor nurses, finding significant differences among the three groups in all the domains analysed.…”
Section: Discussioncontrasting
confidence: 95%
“…These findings partially coincide with other research (Bijani et al ) where justice was the most appreciated value, especially among nursing instructors and nurses, followed by the values directly related to care. If we compare this with our study, ethical values are most important.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results revealed Table 6. Frequency of VAS score at hour12 in normal saline group based on education level score N (%) illiterate Below diploma diploma academic P value that intravenous injection of magnesium sulfate during cesarean section in patients undergoing spinal anesthesia reduced postoperative analgesic consumption and relieved postoperative pain (41).…”
Section: Discussionmentioning
confidence: 99%